The principal's effectiveness in student achievement in Peruvian schools - Rivera, Jairo (2020)
The current investigation analyzes the effect that the school principal has had on the performance of students. It begins with a review of the literature on the effectiveness of the principal, its characteristics and its particularities in Peru. Then, it develops the empirical section by using longitudinal data from the Young Lives program and its School Survey; and by using educational production functions, implementing instrumental variables, it estimates the effect of the principal on students’ performance on standardized tests of mathematics and language. The principal outcome of the study is linked to a positive effect of the principal on student performance, with an important magnitude, associated with the characteristics of a developing country.